A method for preparing biodegradable plastic
A biodegradable plastic composition using PLA, PBS, cotton linters, modified flax fibers, and montmorillonite powder, along with a degradation aid, addresses the performance limitations of existing plastics by improving mechanical strength and biodegradability through a specialized processing method.
Patent Information
- Application Number
- CN202311089635.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-11-10
AI Technical Summary
Existing biodegradable plastics suffer from low tensile strength, poor weather resistance, and inadequate comprehensive performance, failing to meet the demands of special plastic applications.
A biodegradable plastic composition comprising PLA and PBS as a mixed plastic matrix, combined with cotton linters, modified flax fibers, montmorillonite powder, and a degradation aid of cephalosporin, starch, and wood ash, processed through a specific melt-blending and extrusion method to enhance mechanical properties and biodegradability.
The solution results in a biodegradable plastic with improved mechanical properties and accelerated degradation, facilitated by the synergistic effects of the filler materials and degradation aids, enhancing the plastic's stability and biodegradability.
Smart Images

Figure BDA0004417265910000021 
Figure BDA0004417265910000061 
Figure BDA0004417265910000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmentally friendly degradable materials, and in particular to a method for preparing biodegradable plastics. Background Art
[0002] Since its birth, plastic has rapidly entered human life and industrial and agricultural production with its excellent properties such as light weight, high strength, corrosion resistance and low price, and has been widely used. However, with the rapid growth of plastic production, the post-processing of waste plastics and the environmental pollution caused by them have attracted more and more attention from all countries. Environmental pollution caused by plastic waste has become a global problem. Developing degradable plastics is an effective way to solve plastic pollution.
[0003] As people's environmental awareness increases, environmentally friendly and degradable materials are becoming more and more popular. Bioplastics have the advantages of not using petroleum products to make them and self-decomposing after use, and are about to replace traditional plastics and enter our lives. Bioplastics refer to plastics produced by microorganisms based on natural substances such as starch. They are renewable and therefore very environmentally friendly. In the prior art, some people use corn starch and potato starch as raw materials. The prior art uses a twin-screw extruder to apply pressure to the starch through the screw at a certain temperature, so that the protein therein is modified and extruded into a degradable plastic; however, the degradable plastic specimens obtained by the above method have defects such as low tensile strength, poor weather resistance, and low comprehensive performance, and their comprehensive performance is difficult to meet the needs of special plastics.
[0004] In the existing research on biodegradable plastics, Run Mingtao et al. used hyperbranched polyamide ester as a nucleating agent to modify PBS by melt blending. With the increase of hyperbranched polyamide ester content, the impact strength, storage modulus and elasticity of the composite material increased slightly, while T g Slightly decreased. Li Jiwei et al. filled hollow glass microspheres into PBS to prepare composite materials. With the increase of the content of hollow glass microspheres, the crystallization rate, tensile elastic modulus and thermal stability of the composite materials increased, but the crystal structure did not change. When the mass fraction of hollow glass microspheres increased from 5% to 20%, the storage modulus and complex viscosity of the composite materials increased, while the density decreased monotonically.
[0005] As consumers gradually shift their preference for plastic products, renewable and environmentally friendly materials are increasingly sought after by the market, and the market demand for bio-based plastics is increasing. Some scientific research institutions in my country have conducted research and trials on biodegradable plastics, but they have not been widely recognized or mass-produced. Based on the above statement, the present invention proposes a biodegradable plastic and a preparation method thereof. Summary of the invention
[0006] In view of the problems described in the above background technology, the present invention aims to provide a method for preparing a biodegradable plastic, which has degradability that meets the standards while meeting the practical requirements of plastic specimens.
[0007] To achieve the above object, the present invention proposes the following technical solutions:
[0008] A biodegradable plastic comprises the following raw materials in parts by weight:
[0009]
[0010] On the basis of the above scheme and as a preferred scheme of the above scheme, the mixed plastic is a blend of PLA and PBS, and the ratio of PBS:PLA is (65-85):(15-35) in percentage.
[0011] On the basis of the above scheme and as a preferred scheme of the above scheme, it is characterized in that the specifications of the PLA are: density is 1.24g / cm 3 , melt flow rate is 5g / 10min (2.16kg, 210℃); PBS specification is: 1.26g / cm 3 , the melt flow rate is 25 g / 10 min (2.16 kg, 210°C).
[0012] On the basis of the above scheme and as a preferred scheme of the above scheme, the length of the cotton linters is 3.0±1.0 mm and the diameter is 20-30 um; the length of the modified flax fibers is 5.0±1.0 mm and the diameter is 15-25 um, and the modified flax fibers are obtained by immersing flax fibers in a graphene oxide aqueous solution and then drying them.
[0013] On the basis of the above scheme and as a preferred scheme of the above scheme, the degradation aid is a mixture of cephalosporin, starch and wood ash, and the mass ratio thereof is 1:1:1.
[0014] On the basis of the above scheme and as a preferred scheme of the above scheme, the method for preparing the biodegradable plastic is characterized by comprising the following steps:
[0015] S1. Raw material preparation
[0016] PLA and PBS are dried at low temperature respectively, and then melt blended in an internal mixer; cotton linters, modified flax fibers and montmorillonite powder are dried at low temperature at the same time;
[0017] S2. Pre-mixing and mixing
[0018] PLA and PBS are blended in a certain mass ratio, melt-blended in an internal mixer for 10-20 minutes, at a blending temperature of 190°C and a rotation speed of 80r / min, and then the mixer is stopped and unloaded to obtain a premixed raw material;
[0019] Meanwhile, cotton linters, modified flax fibers, and montmorillonite powder are equally divided into the same number of portions according to the usage amount, and placed in the same container to obtain a premixed filler;
[0020] S3. Preparation of biodegradable plastics
[0021] The premixed raw materials are equally divided into two times the number of the premixed fillers, and melt-blended, extruded, granulated and dried through a co-rotating twin-screw extruder to obtain biodegradable plastics.
[0022] On the basis of the above scheme and as a preferred scheme of the above scheme, the low-temperature drying described in step S1 is drying at 50-70° C. for 8-24 hours.
[0023] On the basis of the above scheme and as a preferred scheme of the above scheme, in step S3, the order of adding the premixed raw materials and the premixed fillers for the first time is "premixed raw materials-cotton linters-premixed raw materials-montmorillonite powder-modified flax fiber".
[0024] On the basis of the above scheme and as a preferred scheme of the above scheme, in step S3, the melt blending extrusion, granulation and drying process of the premixed raw materials and the premixed fillers are repeated at least three times before injection molding.
[0025] On the basis of the above scheme and as a preferred scheme of the above scheme, in step S3, the operating temperature of each section of the twin-screw extruder is 190-280°C, and the screw speed is 230-300r / min.
[0026] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0027] The invention discloses a biodegradable plastic and a preparation method thereof. The biodegradable property of a mixed plastic matrix and the biodegradable properties of fillers such as cotton linters and modified flax fibers are utilized to make the plastic as a whole biodegradable. Meanwhile, the cotton linters, modified flax fibers and montmorillonite powder enhance the mechanical properties of the mixed plastic matrix. Degradation aids include cephalosporin, starch and plant ash, which are helpful for the interface bonding between the filler and the matrix during the plastic molding process, thereby improving the stability of the biodegradable plastic of the invention. When the plastic is buried, the degradation aid is firstly pyrolyzed in the environment to increase the organic nitrogen content of the soil, thereby providing a good environment for bacteria, thereby accelerating the biodegradation of the plastic.
[0028] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered part of the present subject matter disclosure to the extent such concepts are not mutually inconsistent.
[0029] The foregoing and other aspects, embodiments and features of the present invention will be more fully understood from the following description. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or will be learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0031] Figure 1 This is a schematic diagram of the principle of PBS and PLA as a mixed matrix when subjected to stress and stretching. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0033] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. Words such as "include" or "comprise" mean that the elements or objects appearing before "include" or "comprise" cover the features, wholes, steps, operations, elements and / or components listed after "include" or "comprise", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0034] At present, the main types of biodegradable resins that can be industrially produced are as follows: PBS, including polybutylene succinate (PBS) and polybutylene terephthalate-adipate (PBAT); polylactic acid (PLA) biodegradable materials; polycaprolactone (PCL) biodegradable materials. PBS biodegradable materials belong to alkyd resins. Their synthesis is mainly through esterification and polycondensation of dibasic acid or dibasic acid dimethyl ester with diol. The main synthesis routes are direct esterification and transesterification. Polylactic acid (PLA) is popular because of its biodegradability and excellent performance. There are two main methods for the synthesis of polylactic acid: direct polycondensation of lactide and ring-opening polymerization of lactide. Polycaprolactone (PCL) is a polymer synthesized in the early 1930s. It has good biodegradability, is non-toxic and harmless to humans, has good flexibility and processability, excellent drug permeability, and good thermal stability. It has better rheological properties and viscoelasticity than other biodegradable materials. The present invention utilizes the biodegradability of the plastic itself and organically selects PBS and PLA as a mixed plastic matrix, which is beneficial to the biodegradability of the entire plastic.
[0035] Specifically, the biodegradable plastic disclosed in the present invention comprises the following raw materials in parts by weight:
[0036] Mixed plastics 100 parts;
[0037] 10-20 parts of cotton linters;
[0038]
[0039] A method for preparing a biodegradable plastic comprises the following steps:
[0040] S1. Raw material preparation
[0041] PLA and PBS are dried at low temperature respectively, and then melt blended in an internal mixer; cotton linters, modified flax fibers and montmorillonite powder are dried at low temperature at the same time;
[0042] S2. Pre-mixing and mixing
[0043] PLA and PBS are blended in a certain mass ratio, melt-blended in an internal mixer for 10-20 minutes, at a blending temperature of 190°C and a rotation speed of 80r / min, and then the mixer is stopped and unloaded to obtain a premixed raw material;
[0044] Meanwhile, cotton linters, modified flax fibers, and montmorillonite powder are equally divided into the same number of portions according to the usage amount, and placed in the same container to obtain a premixed filler;
[0045] S3. Preparation of biodegradable plastics
[0046] The premixed raw materials are equally divided into the same number of portions as the premixed fillers, and melt-blended, extruded, granulated and dried through a co-rotating twin-screw extruder to obtain biodegradable plastics.
[0047] In the present invention, cotton linters are light and easy to float, and are not easy to mix with premixed raw materials. Therefore, in the process of raw material blending injection molding, after adding premixed raw materials to the feed port of the rotating twin-screw extruder, the steps of adding cotton linters in sequence and then adding premixed raw materials can play the role of pushing the cotton linters forward and pressing the material, and then adding montmorillonite powder can further increase the weight on the cotton linters, so that it continues to move forward, and finally adding modified flax fiber, the flax fiber will not have the problem of cotton linters; finally, melt blending extrusion, granulation, and drying processes are carried out multiple times. During the experiment, the melt blending extrusion, granulation, and drying processes are carried out three times at the same time. The materials mixed in the order of adding "premixed raw materials-cotton linters-premixed raw materials-montmorillonite powder-modified flax fibers" are more uniform. The problem of residual feed port of cotton linters will appear in the disordered direct addition and all mixed addition, and the cotton linters or flax fibers on the surface of the extruded plastic particles are prominent.
[0048] Further, the PLA of the present invention was purchased from Nature The specifications of polylactic acid model 2002D are: density 1.24g / cm 3 , the melt flow rate is 5g / 10min (2.16kg, 210℃); further, PBS is purchased from Showa Polymer Co., Ltd. of Japan, and its specification is: 1.26g / cm 3 , the melt flow rate is 25g / 10min (2.16kg, 210°C). Furthermore, in step S3 of the present invention, the operating temperature of each section of the twin-screw extruder is 190-280°C, and the screw speed is 230-300r / min.
[0049] The degradation aid of the present invention is a mixture of cephalosporin, starch and wood ash, and the mass ratio thereof is 1:1:1. After the degradation aid is buried, substances containing structures such as amino acids and amino sugars undergo organic pyrolysis, which can increase the organic nitrogen content of the soil; at the same time, these substances directly or indirectly affect the diversity, abundance and activity of microorganisms during the turnover of nitrogen elements, and then affect the activity of microorganisms in the soil. Adding starch and wood ash is beneficial to the increase of phosphorus in the soil. The combination of the three will affect the chemical behavior and effectiveness of P, and then affect the biodegradability. Its detailed effects can be concluded from the following comparative experiments:
[0050] Take a certain mass of soil containing the same amount of microplastics, and then divide the soil into five groups A / B / C / D / E. Assuming that the mass of each group of soil is 10kg, the first group A is used as the blank control group. The following four groups, B / C / D / E, are added with soil mixed with gradient mass of degradation agents, and the mass of degradation agents contained is 0.05kg, 0.1kg, 0.5kg, and 1kg respectively. After 6 months, the microplastic content of the five groups A / B / C / D / E was measured again. The microplastic content of group A did not decrease significantly, and the microplastic content of the five groups B / C / D / E showed a significant downward trend. When 8% of the degradation agent was added, the degradation capacity of the microplastics in the experimental soil reached its peak.
[0051] Examples 1-3
[0052] Weigh the components shown in Table 1 by weight percentage: PBS, PLA, cotton linters, modified flax fiber, montmorillonite powder, and degradation aid combination. Follow the steps below:
[0053] S1. Raw material preparation
[0054] PLA and PBS are dried at low temperature respectively, and then melt blended in an internal mixer; cotton linters, modified flax fibers and montmorillonite powder are dried at low temperature at the same time;
[0055] S2. Pre-mixing and mixing
[0056] PLA and PBS were blended in a certain mass ratio, melt-blended in an internal mixer for 15 minutes at a blending temperature of 190°C and a rotation speed of 80 r / min, and the mixer was stopped and unloaded to obtain a premixed raw material;
[0057] Meanwhile, cotton linters, modified flax fibers, and montmorillonite powder are equally divided into the same number of portions according to the usage amount, and placed in the same container to obtain a premixed filler;
[0058] S3. Preparation of biodegradable plastics
[0059] The premixed raw materials are equally divided into the same number of portions as the premixed fillers, and melt-blended, extruded, granulated and dried through a co-rotating twin-screw extruder to obtain biodegradable plastics.
[0060] Example 2-3
[0061] Different from Example 1, the materials are mixed and sampled according to weight percentage to obtain corresponding plastics, and samples with corresponding performance test requirements are made.
[0062] Comparative Examples 1-11
[0063] Different from Example 1, materials are mixed and samples are prepared according to the data in Table 1 to obtain corresponding plastics, and samples with corresponding performance test requirements are made.
[0064] Performance Testing
[0065] Mechanical properties
[0066] The plastic particles of the embodiment and the comparative example were made into standard dumbbell-shaped specimens (GB1040-79), and the relevant mechanical properties were tested for comparison of the mechanical properties of the subsequent degraded specimens.
[0067] Biodegradability
[0068] In order to ensure the accuracy of the test data as much as possible, two test methods were used to evaluate the biodegradability of plastics, namely the soil burial method and the microbial growth method.
[0069] Soil burial method
[0070] First, the plastic particles of the embodiment and the comparative example were pressed into 2 mm thin sheets on a flat vulcanizer, and standard dumbbell-shaped specimens (GB1040-79) were punched on the mold. Then the dumbbell-shaped specimens were buried in a container filled with garden soil at a burial depth of 10 cm, and kept at high humidity and away from light. The soil-buried samples were retrieved every other month, and the tensile strength and elongation at break of the samples were measured at 20°C and a tensile speed of 100 mm / min.
[0071] Microbial growth method
[0072] Similarly, the plastic particles of the embodiment and the comparative example were pressed into a film with a thickness of about 0.1 mm on a flat vulcanizer, and cut into uniform samples of 4 cm×4 cm. The two groups of samples were placed on the surface M containing an inorganic salt nutrient medium (one group of which was supplemented with glucose in the nutrient medium at a concentration of 30 g / 1000 m), coated with a layer of microbial suspension (including five microorganisms such as Cercospora serrata, Paecilomyces cerevisiae, Aspergillus niger, Aspergillus flavus and Pseudomonas sp.), cultured at 28°C for 45 days, and the erosion of the samples by the microorganisms was observed. Then, the samples were taken out, the colonies were washed, and vacuum dried at 30°C to constant weight, and the weight loss rate was measured.
[0073] According to the relevant test requirements, the plastic particles of the embodiment and the comparative example were made into standard samples, and the relevant test analysis results are shown in Table 1:
[0074] Table 1 Material ratio and test results analysis table
[0075]
[0076]
[0077] *The degree of erosion is the relative value of the original plastic particles based on the volume comparison gradient divided by the drainage method.
[0078] For mixed plastics, combined with the data in Table 1, the elongation at break of pure PBS is 282.5%, the yield strength is 32.0 MPa, and the tensile strength is 473.1 MPa. When the PLA content increases, the elongation at break of the blend increases. Figure 1 As shown, in the blend stretching process, in addition to the shear band formed by the PBS matrix, which can stop the development of silver streaks, as the stretching process proceeds, the PLA dispersed phase in the mixed plastic blend is continuously transformed from granular to fibrous, which can effectively prevent the transformation of silver streaks to microcracks. The continuous enhancement of the termination ability of silver streaks enables the stretching process of the blend sample to be carried out more stably. In the process of testing the mixed plastic granulation of the two, when the ratio of PBS:PLA is 75:25, its mechanical properties are the best. Therefore, PBS:PLA of the present invention is preferably 75:25.
[0079] Further, according to the similarity between PBS and PLA, cotton linters and flax fibers are natural degradable substances, and their use does not affect the overall degradability. The addition of fillers can prevent the expansion of microcracks and the mechanical properties of fillers are relatively high. Most importantly, due to the impregnation of graphene oxide solution, the modified flax fiber has a layer of graphene oxide film on the fiber surface, which can enhance the interface bonding performance between the filler and the matrix. The active functional groups of graphene oxide can easily form chemical bonds such as hydrogen bonds with the surface of flax fibers, and its structure is stable, which helps to enhance the mechanical properties of the matrix. Montmorillonite powder has the characteristics of high strength, and it is mainly composed of silicate components. It can be used as an inorganic material to enhance the tensile strength, elongation at break, impact strength, bending strength, tensile elastic modulus, Vicat softening point, etc. of the matrix, and its combined effect is also used to improve the degradability.
[0080] In summary, the biodegradable plastic of the present invention is biodegradable, and the added cotton linters, modified flax fibers, montmorillonite powder and a degradation aid combination are beneficial to improving the degradation rate of the plastic.
[0081] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A biodegradable plastic, characterized in that: The invention comprises the following raw materials in parts by weight: Mixed plastics 100 parts; 15-20 parts of cotton linters; 10-15 parts of modified flax fiber; 5 parts of montmorillonite powder; 0.5~10.5 parts of degradation aid; The mixed plastic is a blend of PLA and PBS, and the ratio of PBS to PLA is 65-85:15-35. The degradation aid is a mixture of cephalosporin, starch and plant ash, with a mass ratio of 1:1:1; The modified flax fiber is obtained by immersing the flax fiber in a graphene oxide aqueous solution and then drying it.
2. The biodegradable plastic according to claim 1, characterized in that: The specifications of the PLA are: density is 1.24 g / cm 3 , at 2.16 kg, 210 ° C, the melt flow rate is 5g / 10min; the specification of PBS is: 1.26 g / cm 3 , under the conditions of 2.16 kg and 210°C, the melt flow rate is 25g / 10min.
3. The biodegradable plastic according to claim 1, characterized in that: The length of the cotton linters is 3.0±1.0 mm, and the diameter is 20-30 um; the length of the modified flax fibers is 5.0±1.0 mm, and the diameter is 15-25 um.
4. A method for preparing the biodegradable plastic according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Raw material preparation PLA and PBS are dried at low temperature respectively, and then melt blended in an internal mixer; cotton linters, modified flax fibers and montmorillonite powder are dried at low temperature at the same time; S2. Pre-mixing and mixing PLA and PBS are blended in a certain mass ratio, melt-blended in an internal mixer for 10-20 minutes, at a blending temperature of 190°C and a rotation speed of 80r / min, and then the mixer is stopped and unloaded to obtain a premixed raw material; Meanwhile, cotton linters, modified flax fibers, and montmorillonite powder are equally divided into the same number of portions according to the usage amount, and placed in the same container to obtain a premixed filler; S3. Preparation of biodegradable plastics The premixed raw materials are equally divided into two times the number of the premixed fillers, and melt-blended, extruded, granulated and dried through a co-rotating twin-screw extruder to obtain biodegradable plastics.
5. The method for preparing a biodegradable plastic according to claim 4, characterized in that: The low temperature drying in step S1 is drying at 50-70° C. for 8-24 hours.
6. The method for preparing a biodegradable plastic according to claim 4, characterized in that: In step S3, the order of adding the premixed raw materials and the premixed fillers for the first time is "premixed raw materials-cotton linters-premixed raw materials-montmorillonite powder-modified flax fibers".
7. The method for preparing a biodegradable plastic according to claim 6, characterized in that: In step S3, the premixed raw material and the premixed filler are melt-blended, extruded, granulated, and dried for at least three cycles before injection molding.
8. The method for preparing a biodegradable plastic according to claim 4, characterized in that: In step S3, the operating temperature of each section of the twin-screw extruder is 190-280°C, and the screw speed is 230-300r / min.